Effects of microstructural heterogeneity on very high cycle fatigue properties of 7050-T7451 aluminum alloy friction stir butt welds. (February 2016) - Deng, Caiyan; Wang, Hong; Gong, Baoming; Li, Xiang; Lei, Zhenyu
Highlights: The failure of the friction stir welding joints still occurs at 7.0 × 10 8 cycles. The fatigue properties of the FSW joint are superior to these of the base material. Fatigue crack of the FSW joints often originates at the advancing side. There exists the correlation between metallurgic heterogeneity and fatigue failure. Abstract: In this study, the very high cycle fatigue (VHCF) properties of 7050-T7451 aluminum alloy and its friction stir welding (FSW) butt welds have been investigated. The results show that the failure of FSW joints still occurs at 7.0 × 10 8 cycles. The fatigue properties of the FSW joints are superior to those of the base material, especially in the super long life regime. Most fatigue cracks initiate at the thermo-mechanically affected zone and heat affected zone on the advancing side of the FSW joints, and the susceptibility of these zones to fatigue is attributed to the metallurgical heterogeneity.